2013
DOI: 10.1177/1748895813483762
|View full text |Cite
|
Sign up to set email alerts
|

Community policing and reassurance: Three studies, one narrative

Abstract: Drawing on data from three separate studies of community policing (CP) in Scotland this article identifies common themes in the practice of contemporary CP. First, following in the wake of the global financial crisis, we have an austerity drive with cuts to policing budgets setting the context in which CP practice is now negotiated. Second all three studies evidence an increasingly entrenched performance management framework for policing which exerts pressures on beat officers to depart from established, value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…It is notable that factors such as interacting with and trusting one's neighbors had a slightly greater effect upon feelings of safety than the perceived quality of policing services. Reassurance, therefore, is not simply something to be provided to communities through policing strategies (Innes, ; Hamilton‐Smith, Mackenzie, Henry, & Davidones, ). While some affluent consumers can secure their own reassurance and safety through “withdraw[al] into increasingly insulated enclaves” (Atkinson, , p. 819), those in more deprived communities may have to be enabled to create their own reassurances.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that factors such as interacting with and trusting one's neighbors had a slightly greater effect upon feelings of safety than the perceived quality of policing services. Reassurance, therefore, is not simply something to be provided to communities through policing strategies (Innes, ; Hamilton‐Smith, Mackenzie, Henry, & Davidones, ). While some affluent consumers can secure their own reassurance and safety through “withdraw[al] into increasingly insulated enclaves” (Atkinson, , p. 819), those in more deprived communities may have to be enabled to create their own reassurances.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the effectiveness of community policing has been related to procedural justice because community‐oriented policing strategies positively affect community member satisfaction, perceptions of disorder, and police legitimacy (Gill, Weisburd, Telep, Vitter, & Bennett, ). In the other direction, it has been shown that procedural justice can effectively enhance community policing strategies and raise the perceived legitimacy of the police (Hamilton‐Smith, Mackenzie, Henry, & Davidones, ; Mazerolle, Bennett, Davis, Sargeant, & Manning, ). Improving perceptions of procedural justice through community policing initiatives, or enhancing existing community policing initiatives with an emphasis on procedurally just strategies may be one promising route for improving perceptions of the justice system.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are widely established philosophies which constitute the community policing concept, and characterise the approaches' overarching theme of effective police-public relations (Bennett 1994). A review of community policing literature by Mackenzie and Henry (2009) put forward key components of effective practice, which have appeared (in some degree) consistently in a number of other academic sources (Bennett 1994;Hamilton-Smith et al 2013;Skogan & Hartnett 1999;Skogan & Williamson 2008).…”
Section: Community Policingmentioning
confidence: 99%